ANALISIS MODEL PENDIDIKAN ISLAM BERBASIS EKOLOGI DI SEKOLAH MENENGAH PERTAMA - Riza Awal Novanto; Nur Rahmah Hidayati; El Syifa Maesarah (UIN Sumatera Utara Medan, 2025)
This study aims to analyze the implementation of Ecology-Based Islamic Education and its leading indicators at SMP At-Tin UMP Margasari, emphasizing the Islamic concept of human responsibility as a caliph on earth. Using a qualitative case study approach, in-depth interviews were conducted with the principal and students to explore integrating Islamic values into ecological education. Data were analyzed using NVivo software to facilitate coding and grouping of themes, including